Goals and Objectives of Independent Education - Kazimova Nafisaxon Minovarovna; Adildjonovoy Muzifabonu Abbasxon kizi (Zien Journals, 2022)
This article provides information on how students work with books, what information to get from the book, what to look for when reading a book independently, as a team, how to organize independent work using appropriate methods. given.
Keywords: educational information; textbooks; abstracts; modifications